2003
DOI: 10.1063/1.1634385
|View full text |Cite
|
Sign up to set email alerts
|

Shear force imaging of soft samples in liquid using a diving bell concept

Abstract: We present a reliable and easy-to-use system, with a perfect analogy to a diving bell, to perform tuning fork based shear force microscopy on soft cells in liquid. Using the diving bell concept the tuning fork vibrates in air, while the tip is immersed in solution. In this way Q factors of 200 and higher in liquid are routinely obtained. The force feedback is reliable and stable over hours requiring a minimum adjustment of the set-point during imaging. With this system, tip-sample interaction forces are kept b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 10 publications
0
51
0
Order By: Relevance
“…The rapid decrease in Q with submersion depth ͑D͒ means that even a small height of water will cause significant deterioration in probe Q. This has implications to liquid cell 19 and probe designs aimed at minimizing the immersion depth to Յ100 m or attempting to eliminate the damping effects by creating a diving bell 19,30 to surround the probe except over the last tens of microns.…”
Section: Probe Damping In Watermentioning
confidence: 99%
“…The rapid decrease in Q with submersion depth ͑D͒ means that even a small height of water will cause significant deterioration in probe Q. This has implications to liquid cell 19 and probe designs aimed at minimizing the immersion depth to Յ100 m or attempting to eliminate the damping effects by creating a diving bell 19,30 to surround the probe except over the last tens of microns.…”
Section: Probe Damping In Watermentioning
confidence: 99%
“…Although important biological information can be extracted from NSOM on dry biological samples, these results are always subject to potential drying artifacts (35). We have recently shown that the performance of NSOM can be extended to measurements in liquid environments using a diving bell concept (34), and showed for the first time single molecule detection sensitivity with 90 nm spatial resolution on wet cells (32). To demonstrate the general applicability of NSOM for cell membrane studies in liquid conditions, we have extended our investigation of the organization of DC-SIGN to wet dendritic cells.…”
Section: High-resolution Nsom Imaging In Liquidmentioning
confidence: 99%
“…The probe is kept in the near-field region of the sample (<10 nm) by means of a shear-force feedback based on a piezoelectric element, providing simultaneously a topographic map of the sample surface while scanning (23,24,26). Recently, we have developed a reliable and easy-to-use system, with perfect analogy to a diving bell, to allow NSOM operation under liquid conditions (34). A small glass tube, carefully glued into an aluminum holder, as shown in Fig.…”
Section: Near-field Scanning Optical Microscopy (Nsom)mentioning
confidence: 99%
“…However, current applications of NSOM to biological samples are largely limited to isolated protein samples, model membranes, or chemically fixed biological cells. [2][3][4][5] The extension to viable, unfixed biological tissues has previously proven problematic.…”
mentioning
confidence: 99%
“…These have largely involved either changing the feedback mechanism utilized to hold the tip close to the sample or modifying the probes themselves to lower the spring constant and thus the forces generated in force feedback. 2,5,9 For the latter, an obvious route of exploration is to incorporate a near-field light source onto conventional atomic force microscopy ͑AFM͒ cantilevers.9-11 AFM is widely used in biological applications on unfixed tissues under physiological conditions.Commercially available silicon nitride AFM cantilevers come in a variety of geometries that offer a range of cantilever spring constants and tip parameters. Using these tips, AFM techniques have been widely utilized for studies of sample surfaces, including living cells, while operating with the AFM tip either directly in contact with the sample surface or through a tapping, or intermittent, contact mode of force mapping.…”
mentioning
confidence: 99%